PENGARUH FILM ANIMASI UPIN DAN IPIN TERHADAP PEMBENTUKAN SELF CONCEPT SISWA DI SDN 5 PADANGLAMPE KABUPATEN PANGKEP - Hayana Hayana (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2018)
This study focuses on studying the meaning of the messages contained in the animated films Upin and Ipin and the influence of Upin and Ipin's animated films on the self concept formation of Padanglampe 5 Elementary School students. The purpose of this study was to find out the meaning of the message and the influence of Upin and Ipin animated films on the self concept formation of students at SDN 5 Padanglampe. This research was carried out at SDN 5 Padanglampe kec. Ma'rang, Pangkep district. The research method used is the experimental research method (Research Experiment) with a quantitative approach. Experimental research aims to investigate the causal relationship by exposing one or more experimental groups. The results showed that there were several scenes in the animated film Upin and Ipin which gave a labeling scene and the average labeling given was positive. The more often someone puts a positive word on someone else, then the person given the labeling has a positive self concept for him. Besides the results of the correlation test on students' self concept formation rxy = 0.644> r = table = 0.361 then the hypothesis H0 is rejected and H1 is accepted. This means that H1 is accepted, namely there is the influence of Upin and Ipin animated films on students' self concept at SDN 5 Padanglampe, Pangkep district.